Bioactive peptides derived from egg proteins: A review. Issue 15 (13th October 2018) - Liu, Ya-Fei; Oey, Indrawati; Bremer, Phil; Carne, Alan; Silcock, Pat
ABSTRACT: Egg proteins have various functional and biological activities which make them potential precursor proteins for bioactive peptide production. Simulated in vitro gastrointestinal digestion and enzymatic hydrolysis using non-gastrointestinal proteases have been used as tools to produce these peptides. Bioactive peptides derived from egg proteins are reported to display various biological activities, including angiotensin I-converting enzyme (ACE) inhibitory (antihypertensive), antioxidant, antimicrobial, anti-inflammatory, antidiabetic and iron-/calcium-binding activities. More importantly, simulated in vitro gastrointestinal digestion has indicated that consumption of egg proteins has physiological benefits due to the release of such multifunctional peptides. This review encompasses studies reported to date on the bioactive peptide production from egg proteins.